Gender Equality Issues in Optical Feminist Jurisprudence and Implementation in Indonesian - Heri Setiawan; Steven Ouddy; Mutiara Girindra Pratiwi (Universitas Lampung, 2018)
Gender meaning of fundamentally different from biological sex. Biological sex is a gift; we are born as a man or a woman. However, the path that makes us masculine or feminine is a combination of the building blocks of basic biological and biological interpretation by our culture. From the tiny baby to reach old age, we learn and practice specific ways that have been determined by the community for us to be men and women. Gender is a set of roles as well as costumes and masks at the theater, convey to others that we are feminine or masculine. Device specific behaviors include appearance, dress, attitude, personality, work inside and outside the household, sexuality, family responsibilities and so together polish